Not with a Bang - Booch, G. (IEEE software, 2009)
Software-intensive systems, like bridges and societies, are subject to collapse. Collapse isn't necessarily inevitable, however, but avoiding it requires active, vigorous, and intentional intervention by the system's architects. Two patterns and one antipattern can help architects address the systemic issues that, left unattended, may lead to collapse.